Measurement of Nucleotide Pools in Platelets Using High Pressure Liquid Chromatography - D’Souza, Leo; Glueck, Helen I. (Thrombosis and Haemostasis, 1977)
We have devised an improved high pressure liquid chromatographic technique whereby serotonin, nucleosides, cyclic nucleotides, namely cAMP and cGMP, and 5’ mono-, 5’ di-, and 5’ tri-nucleotides can be analyzed. The cyclic nucleotides have been measured in pico molar quantities. All nucleotides can be quantitated in a single step separation in 75 min using a 0.0015 M phosphoric acids vs. 1 M pH 4.8 ammonium phosphate gradient. 5/10 ml of platelet-rich plasma furnishes an adequate sample for complete analysis. Nucleotide levels in platelets from 16 normal donors expressed in 1011 platelets are as follows: cAMP, 6.32 (4.15) nanomoles and AMP, 0.32(0.14); ADP, 2.48 (0.67); ATP 3.78 (0.68); GDP 0.38 (0.07) and GTP, 0.45 (0.07) micromoles. ADP and ATP values are lower than those previously published. However, the total nucleotide level approaches published values.Upon aggregation with thrombin, approximately 50% of ADP and 40 % ATP is released. Release is complete by 2 min. Thrombin is the most potent releasing agent with collagen and ADP occupying an intermediate role and epinephrine being the least effective. Upon aggregation cyclic AMP levels diminish along with other nucleotides. Patients with asthma showed depression of ADP, ATP, GDP and GTP levels.